Noradrenergic Blockade of Memory Reconsolidation: A Failure to Reduce Conditioned Fear Responding - Bos, Marieke Geerte Nynke; Beckers, Tom; Kindt, Merel (Frontiers in Behavioral Neuroscience, 2014)
Upon recall, a memory can enter a labile state in which it requires new protein synthesis to restabilize. This two-phased reconsolidation process raises the prospect to directly target excessive fear memory as opposed to the formation of inhibitory memory following extinction training. In our previous studies, we convincingly demonstrated that 40 mg propranolol HCl administration before or after memory reactivation eliminated the emotional expression of fear memory indexed by the fear-potentiated startle reflex. To apply this procedure in clinical practice it is important to understand the optimal and boundary conditions of this procedure. As part of a large project aimed at unraveling putative boundary conditions of disrupting reconsolidation of associative fear memory with propranolol HCl, we again tested our memory reconsolidation procedure. Participants (N = 44) underwent a three-day differential fear conditioning procedure. Twenty-four hours after fear acquisition, participants received 40 mg propranolol HCl prior to memory reactivation. The next day, participants were subjected to extinction training and reinstatement testing. In sharp contrast to our previous findings, propranolol HCl before memory reactivation did not attenuate the startle fear response. Remarkably, the startle fear response even persisted during extinction training and did not show the usually observed gradual decline in conditioned physiological responding (startle potentiation and skin conductance) upon repeated unreinforced trials. We discuss these unexpected findings and propose some potential explanations. It remains however unclear why we observed a resistance to reduce conditioned fear responding by either disrupting reconsolidation or extinction training. The present results underscore that the success of human fear conditioning research may depend on subtle manipulations and instructions.